The Monotonicity Problem in Finding Roots of Polynomials by Kuhn's Algorithm (Journal of Computational Mathematics, 1983)
In this paper the problem proposed by Kuhn on the presence of a monotonicity property related to the Kuhn's algorithm for finding roots of a polynomials is solved in the affirmative. Furthermore, an estimate of the threshold number D in the above-mentioned monotonicity problem expressed in terms of the complex coefficients of the polynomial is obtained.